2011
DOI: 10.1590/s0074-02762011000200012
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of meta 1 expression with culture stage, cell morphology and infectivity in Leishmania (Leishmania) amazonensis promastigotes

Abstract: The parasitic protozoan Leishmania (Leishmania)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Moreover, during the stationary phase promastigotes with small bodies and large flagella could be clearly identified by optic microscopy (data not shown); these were confirmed by flow cytometry (Figure 2D) as FSC lo PI - cells [33,34]. Based on this typical morphology of metacyclic promastigotes, we analyzed metacyclogenesis throughout the 6 days of culture by quantifying the expression of specific genes which are upregulated ( Meta-1 and SHERP ) or downregulated ( histone H4 ) during the process [25,33,35] (Figure 3 and Additional file 5: Figure S4). Despite the observed interstrain variations on the fold modifications of each gene, all of the strains showed a dramatic decrease in histone H4 expression consistent with the cell cycle analysis.…”
Section: Resultsmentioning
confidence: 82%
“…Moreover, during the stationary phase promastigotes with small bodies and large flagella could be clearly identified by optic microscopy (data not shown); these were confirmed by flow cytometry (Figure 2D) as FSC lo PI - cells [33,34]. Based on this typical morphology of metacyclic promastigotes, we analyzed metacyclogenesis throughout the 6 days of culture by quantifying the expression of specific genes which are upregulated ( Meta-1 and SHERP ) or downregulated ( histone H4 ) during the process [25,33,35] (Figure 3 and Additional file 5: Figure S4). Despite the observed interstrain variations on the fold modifications of each gene, all of the strains showed a dramatic decrease in histone H4 expression consistent with the cell cycle analysis.…”
Section: Resultsmentioning
confidence: 82%
“…The mRNA expression and arginine uptake were evaluated along the growth curve by maintaining the parasites at log phase by sub-culturing them every 24 h with the same initial cell ratio (5×10 5 parasites/mL), as previously described [44].…”
Section: Methodsmentioning
confidence: 99%
“…A 7300 System (Applied Biosystems, USA) was used to run the qRT-PCR. The primers used to amplify GAPDH (internal control), arginase and SSUrRNA are described elsewhere [44].…”
Section: Methodsmentioning
confidence: 99%
“…Transcriptomic and proteomic data compiled in S2 Table indicate stage-specific expression for additional Class I and II "CEST-like" molecules in trypanosomatids [50, 63, 66]. Interestingly, META proteins were shown to be involved in Leishmania growth and infectivity [58, 64, 65]. Our present results show a somehow related sub-cellular localization and growth phenotype for TCLP 1.…”
Section: Discussionmentioning
confidence: 55%
“…In the same line, it was reported that META1, a conserved Leishmania virulence factor display distant homology and structural similarity to Shigella MxiM, an outer membrane protein required for TIIISS-mediated effector translocation [58, 61]. Interestingly, META1 and other related molecules display several structural and functional features similar to TCLP 1 [6265]. On one hand, their expression profiles are not homogeneous along the parasite life-cycle, suggesting they are under certain developmental regulation program.…”
Section: Discussionmentioning
confidence: 96%